2008
DOI: 10.1016/j.jneumeth.2007.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Physiological glucose is critical for optimized neuronal viability and AMPK responsiveness in vitro

Abstract: Understanding the mechanisms that govern neuronal responses to oxidative and metabolic stress is essential for therapeutic intervention. In vitro modeling is an important approach for these studies, as the metabolic environment influences neuronal responses. Surprisingly, most neuronal culture methods employ conditions that are non-physiological, especially with regards to glucose concentrations, which often exceed 20 mM. This concentration is a significant departure from physiological glucose levels, and even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 63 publications
0
58
0
Order By: Relevance
“…However, glucose levels found in cell cultures (designed for rapid cell growth) far exceed physiological levels, often containing >20mM glucose. In severe hyperglycemia plasma levels may reach 15.2mM, and in hypoglycemia, may drop to 2.8mM, while brain levels only reach 4.5mM, or fall as low as 0.16mM 41 . As such, neurons in culture are consistently exposed to >10 times the levels found in vivo .…”
Section: Improving Current Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, glucose levels found in cell cultures (designed for rapid cell growth) far exceed physiological levels, often containing >20mM glucose. In severe hyperglycemia plasma levels may reach 15.2mM, and in hypoglycemia, may drop to 2.8mM, while brain levels only reach 4.5mM, or fall as low as 0.16mM 41 . As such, neurons in culture are consistently exposed to >10 times the levels found in vivo .…”
Section: Improving Current Modelsmentioning
confidence: 99%
“…In vivo , plasma glucose can range from 5.5 to 7.8mM, while brain glucose levels have been reported ranging from 0.82 to 2.4mM 41 , 42 . However, glucose levels found in cell cultures (designed for rapid cell growth) far exceed physiological levels, often containing >20mM glucose.…”
Section: Improving Current Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the pharmacological inhibition or gene deletion of AMPK can be neuroprotective in stroke (70,78). The discrepancies between in vivo and in vitro studies elucidating the role of AMPK in neuronal survival (28,78) could be due to differences in glucose concentrations, which has been previously shown to be critical for determining neuronal survival and the levels of AMPK activation (62,91). Therefore, by using the similar metabolic conditions our laboratory has further explored the protective versus cell death-inducing effects of AMPK activation in neurons exposed to metabolic stress, as exemplified in a model of excitotoxic Ca 2þ overloading.…”
Section: Ampk Activation In Cerebral Ischemia and Excitotoxicitymentioning
confidence: 99%
“…We found that hyperglycemic conditions (>10 mM glucose) for neuronal cells in culture suppressed SelS mRNA and protein levels. SelS expression was greatest at a glucose concentration near the normal range in brain (5 mM) [25] and decreased as glucose increased (Fig. 1C, above) [10, 11, 21].…”
Section: Resultsmentioning
confidence: 99%